2015
DOI: 10.4314/gjass.v14i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cost efficiency in food crop production among small-scale farmers in Adamawa state, Nigeria

Abstract: Efficient allocation of resources has been a problem in small holder farm economy in Nigeria. The study analyzes cost efficiency in food crop production among small-scale farmers in Adamawa State, Nigeria. Specifically, the socioeconomic characteristics of food crop farmers in the study area were described, their various cropping systems identified and the cost efficiency indices of the farmers determined. Data were collected from 360 randomly selected food crop farmers in eight local government areas spread a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 5 publications
12
14
0
Order By: Relevance
“…The years of farming experience has a significant influence on the decision making of farmers with respect to risk aversion, adoption of improved agricultural technologies and other production related decisions. This finding is in line with [14] who reported that years of farming experience improve productivity and overall efficiency in food crop production in their study on analysis of technical inefficiency in food crop production systems among small-scale farmers in some selected local government areas of Adamawa State. This result also conformed to the result obtained by [15] who indicated 53% of the farmers have been producing for more than 20 years in Kaduna State.…”
Section: Socio-economic Characteristics Of Rice Farmerssupporting
confidence: 89%
“…The years of farming experience has a significant influence on the decision making of farmers with respect to risk aversion, adoption of improved agricultural technologies and other production related decisions. This finding is in line with [14] who reported that years of farming experience improve productivity and overall efficiency in food crop production in their study on analysis of technical inefficiency in food crop production systems among small-scale farmers in some selected local government areas of Adamawa State. This result also conformed to the result obtained by [15] who indicated 53% of the farmers have been producing for more than 20 years in Kaduna State.…”
Section: Socio-economic Characteristics Of Rice Farmerssupporting
confidence: 89%
“…The inefficiency models revealed that socio economic variables, namely: family size, farming experience, gender and extension contact has significantly reduce cost inefficiency among the farmers. Maurice et al (2015) employed stochastic frontier cost function to analyze and determine the cost efficiency in food crop production among small-scale farmers in Adamawa State, Nigeria. The result of the maximum likelihood estimates of the stochastic frontier cost function revealed that the explanatory variables: extension contact, crop diversification and credit availability were significantly and positively related to the cost efficiency in the study area.…”
Section: Conceptual and Theoretical Frameworkmentioning
confidence: 99%
“…In a study in Adamawa State of Nigeria Maurice et al . () found technical efficiency to average 66% among food‐producing small‐scale farmers. They identified 11 cropping systems which included mixed cropping.…”
Section: Methodsmentioning
confidence: 99%
“…It is measured as a ratio of actual to potential output (Donkoh et al, 2013). This is the ratio of the farm's actual output to its maximum frontier output for a given level of inputs and chosen technology (Maurice et al, 2015). An efficient producer is one who produces the maximum possible (potential) output given a set of inputs or one who uses the least inputs in producing a given output.…”
Section: Literature Review On Sfamentioning
confidence: 99%
See 1 more Smart Citation